End-of-Life Vehicle Directive: A Key Element to the Vehicle Design Process - Mat Saman, Muhamad Zameri; Zakuan, Norhayati (2006)
Nowadays, industrial countries are faced with the consequence of a wide diffusion of consumer goods and shortening of product lifetime, giving rise to an increasing quantity of used products being discarded. This phenomenon will increase the problem of the disposal of used products, with the capacity of landfill sites quickly reducing. Current legislation in many developed countries is increasingly guided by the originator principle, which means that anyone who inflicts harm on the environment should pay for cleaning up the damage and, in turn, will compel manufacturers to undertake efforts of recycling at the end-of-life of their products. This has huge implications on the end-user, the manufacturer and recyclers. As such, environmental issues should be accountable throughout the whole life cycle of a product, i.e. it’s design, manufacture, use, service and it’s end-of-life. Indeed, it is becoming increasingly important that considerations are given to the disassembly of a product that can allow complete material recycling, along with possible part and subassembly reuse. Hence, this paper discusses the impact of the End-of-Life Vehicle (ELV) Directive in the current environment. It summarises the current literature published in the field. In particular, the implication ELV has on current product design practice is explored. The result of the literature review shows that, in order to successfully implement the concept of ELV, the aspects of disassembly, recycling and environment must be considered more rigorously in the vehicle design process.